Peningkatan Akses Informasi Teknologi Pemasaran UMKM Makanan Olahan Kota Singkawang - Sandini, Sari; Nurliza, Nurliza; Fitrianti, Wanti (Jurnal Social Economic of Agriculture, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in driving the wheels of the community's economy, serving as a foundation for generating income for their livelihoods. However, many actors in the food MSME sector still face challenges due to their low ability to access marketing technology information. The aim of this study is to formulate improvements in the access to marketing technology information for food MSMEs. This research employs a quantitative descriptive method with Multidimensional Scaling on 58 food MSMEs in Singkawang City. The results indicate that the key attributes for enhancing access to marketing technology information are the content of marketing technology messages and the channels of marketing technology information.